The challenges of community nursing in Europe with a focus on health advice patient education, digital education and the potential of telecare in nursing and nursing education - Adrienn (Magyar Gerontológia, 2025)
European health systems face accelerating population ageing, rising multimorbidity, and persistent workforce shortages, with primary care and community services under increasing pressure.